The development of emotional intelligence through visual plastic strategies in children from 4 to 6 years old: The development of emotional intelligence through visual plastic strategies in children from 4 to 6 years old - Ramírez Pinargote, Johanna Griselda; Quishpe Caranqui, Ricardo Gustavo; Simbaña Chicaiza, Silvia Verónica; Romo García, Mireya Victoria; Almeida Urrea, Laura Elizabeth (LATAM Revista Latinoamericana de Ciencias Sociales y Humanidades, 2025)
The purpose of this research is focused on the development of emotional intelligence by visual plastic strategies in children from 4 to 6 years old, the same one that is directed to the line of research linked to the National Development Plan “Creation Plan of Opportunities 2021-2025”, in particular, it is related to objective 7, which seeks to strengthen the capacities of citizenship, and promote an innovative, inclusive, and quality education at all levels. Its purpose is to enhance the teaching-learning process in the early years of schooling, laying solid foundations for the educational development of boys and girls. These strategies comprise artistic techniques, and approaches that foster children's creativity and imagination, promoting their personal expression, visual perception, and emotional exploration; in turn, emotional intelligence in infants is defined as the ability to identify, understand, and regulate both their own emotions and those of others, which facilitates problem- solving. This research was developed within a methodological design based on a non-experimental approach, aligned with the pragmatic paradigm and with a mixed methodology (qualitative and quantitative). A bibliographic-documentary and field research were used, with a descriptive scope, which allowed us to approach the topic of study in depth and, at the same time, to characterize the population and sample analyzed. Observation of the population sample was carried out with the purpose of gathering information, which was later analyzed and interpreted to understand the problem. The results revealed that educators, due to lack of knowledge, tend to limit the implementation of artistic activities, which significantly reduces their use in the classroom. In conclusion, plastic and visual strategies have a positive impact on the development of emotional intelligence in children since they promote self-awareness and contribute to their integral development. In addition, they strengthen interpersonal relationships with their peers and their environment, providing a solid foundation for their personal growth and daily life.